Has the COVID‐19 pandemic made us more materialistic? The effect of COVID‐19 and lockdown restrictions on the endorsement of materialism. Issue 5 (24th January 2022) - Moldes, Olaya; Dineva, Denitsa; Ku, Lisbeth
Abstract: The COVID‐19 pandemic has led to an increase in the factors that typically facilitate the endorsement of materialistic values (e.g., higher media consumption, stress and anxiety, loneliness, death anxiety, and lower moods). In this paper, we examine how contextual changes affecting the antecedents of materialism influence its advocacy with a mixed‐method approach. First, a correlational study (Study 1) suggests that increases in media consumption and stress and anxiety during the pandemic predicted current levels of materialism, however, these effects were limited. Second, contrary to our expectations, a longitudinal study (Study 2) shows that people's focus on money decreased during the pandemic. Last, a social media content analysis (Study 3) reveals a downward trend in users' online discourses about consumption‐related behaviors, but an upward trend in brands promoting spending as a way to attain well‐being. The observed effects could fuel deeper societal change in the labor market and in consumer behavior, and have further implications for individual and societal well‐being in a post‐pandemic world. We recommend future interventions aimed at diminishing materialistic attitudes to examine the effects of decreasing media consumption and to explore how other factors introduced by the pandemic (e.g., a health or well‐being focus) might moderate its advocacy.